A new species of picture-winged flies of the genus Euphara Loew (Diptera, Ulidiidae) - Hernández-Ortiz, Vicente; Dzul-Cauich, José F. (Zootaxa, 2021)
Based on a large series of specimens found in several localities in Mexico Euphara loculata n. sp. is described. It is the second species of this Neotropical genus, and includes for the first time a description and illustration of the male and female genitalia of the genus.